Morphological and molecular characterization of Penicillium rubens sp.nov isolated from poultry feed - Sawant, Amol M.; Vankudoth, Ramu; Navale, Vishwambar; Kumavat, Rajkamal; Kumari, Prabla; Santhakumari, B.; Vamkudoth, Koteswara Rao (Indian Phytopathology, 2019)
Fungi are the second largest group of eukaryotic organisms, estimates ranging from 2.2 to 3.8 million and 120,000 currently accepted species. Unfortunately, identification of Penicillium species is an overwhelming task even for taxonomic experts. In the current study, we isolated identified and morphologically characterized Penicillium rubens strain NCIM-1397. Molecular characterization of P. rubens by multilocus sequence analysis (MLSA) of internal transcribed spacer (ITS) region, β-tubulin (BenA), calmodulin (CaM), NL (D1/D2 region) and LR (large subunit region) gene. Conversely, BenA gene differentiated P. rubens from P. chrysogenum. Moreover, Vitek MS, Matrix-assisted laser desorption ionization–time of flight mass spectrometer (MALDI-TOF–MS) failed to discriminate to strain level. Metabolic profiling of P. rubens enable to produce roquefortine C, chrysogine, meleagrine, sorbicillin and non-producers for industrially important metabolite, penicillin determined by LC–MS. Even, In addition, even molecular detection of penicillin biosynthetic pathway genes, PcbC, PenDE and Phl were negative by PCR. Nevertheless, P. rubens showed 90–100% toxicity/pathogenicity on seed germination of sorghum (Sorghum bicolor) and no further development of coleoptiles, radicle and leaf length observed. Also, it showed non-toxic to animal cell determined on Human foreskin fibroblast (HFF) cell line by In-Vitro.

Maltooligosaccharide forming amylases and their applications in food and pharma industry - Shinde, Vidhya K.; Vamkudoth, Koteswara Rao (Journal of Food Science and Technology-Mysore, 2022)
Oligosaccharides are low molecular weight carbohydrates with a wide range of health benefits due to their excellent bio-preservative and prebiotic properties. The popularity of functional oligosaccharides among modern consumers has resulted in impressive market demand. Organoleptic and prebiotic properties of starch-derived oligosaccharides are advantageous to food quality and health. The extensive health benefits of oligosaccharides offered their applications in the food, pharmaceuticals, and cosmetic industry. Maltooligosaccharides and isomaltooligosaccharides comprise 2-10 glucose units linked by alpha-1-4 and alpha-1-6 glycoside bonds, respectively. Conventional biocatalyst-based oligosaccharides processes are often multi-steps, consisting of starch gelatinization, hydrolysis and transglycosylation. With higher production costs and processing times, the current demand cannot meet on a large-scale production. As a result, innovative and efficient production technology for oligosaccharides synthesis holds paramount importance. Malto-oligosaccharide forming amylase (EC 3.2.1.133) is one of the key enzymes with a dual catalytic function used to produce oligosaccharides. Interestingly, Malto-oligosaccharide forming amylase catalyzes glycosidic bond for its transglycosylation to its inheritance hydrolysis and alternative biocatalyst to the multistep technology. Genetic engineering and reaction optimization enhances the production of oligosaccharides. The development of innovative and cost-effective technologies at competitive prices becomes a national priority.
Keywords: Glycosyl hydrolases; Isomaltooligosaccharides; Maltooligosaccharide; Maltooligosaccharide forming amylase; Transglycosylation

Metabolites from lactococcus lactis subsp. lactis: isolation, structure elucidation, and antimicrobial activity - Navale, Vishwambar D.; Borade, Balasaheb R.; Rama Krishna, Gamidi; Vamkudoth, Koteswara Rao; Kontham, Ravindar (ACS Omega, 2023)
Herein, we disclose the identification of novel metabolites from a potential probiotic strain, Lactococcus lactis subsp. lactis, obtained from traditional dairy milk samples collected in Maharashtra, India (in January 2021). Isolated metabolites include pyrazin-2-carboxamide [1, pyrazinamide, a potential antitubercular drug], 3,5-dihydroxy-6-methyl-2,3-dihydro-4H-pyran-4-one (2, DDMP), 2,4-di-tert-butylphenol (3), and hexadecanoic acid (4, palmitic acid). The chemical structures of these metabolites were elucidated through extensive 1D NMR (H-1 and C-13) and 2D NMR (HSQC, HMBC, and NOESY) analyses, high-resolution mass spectrometry, high-performance liquid chromatography, and single-crystal X-ray crystallography. Furthermore, these novel metabolites exhibited potent inhibitory activities against various bacteria, fungi, and yeast strains with minimum inhibitory concentrations ranging between 1.56 and 25 mu g/mL, and compounds 1 and 3 were found to be most active against a wide range of microbial strains tested.